Community Assembly in Wastewater-Fed Pilot-Scale Microbial Electrolysis Cells - Cotterill, Sarah E.; Dolfing, Jan; Curtis, Thomas P.; Heidrich, Elizabeth S. (Frontiers in Energy Research, 2018)
The formation of an electrochemically active biofilm is critical to the function of a Microbial Electrolysis Cell (MEC). We used Illumina 16S rDNA sequencing to analyse the formation and composition of anodic biofilms of two pilot-scale MECs, operated in continuous flow mode on domestic wastewater for over six months, and inoculated with that same wastewater. We observe: (i) a clear correlation between the frequency of detection of taxa in the MECs and their abundance in the metacommunity, (ii) the existence of a “core community” that was present across sites and (iii) the percentage of Geobacter tended to increase with longevity of retention time of the wastewater in the reactor. This suggests that: (i) community composition was largely governed by stochastic processes, (ii) that the technology should work on most if not all domestic wastewaters, as long as the anodes are seeded with the target wastewater and (iii) that deterministic factors may also play a role in establishing the anodic community. Geobacter, the archetypical electrogen in bioelectrochemical systems, comprised only 1.0 ± 0.7 % of the sequences recovered from a functioning pilot-scale MEC anode. Our results imply that influent flow rate may need to be optimised separately for start-up and for operating conditions for maximal performance.